Orthoclads of tribe Orthocladiini (Diptera: Chironomidae) from India. - Bhattacharyay, Samapti; Ali, Arshad; Chaudhuri, P. K. (Beiträge zur Entomologie = Contributions to Entomology, 1991)
Acht neue Arten werden aus Indien beschrieben: Cricotopus (Isocladius) ateritarsus, Eukiefferiella lehmanni, E. saccularis, Orthocladius (Eudactylocladius) androgynus, O. (Orthocladius) deflectus, O. (O.) uniradialis, Rheocricotopus (Psilocricotopus) bicornuatus, R. (P:) frequens. Bestimmungstabellen zum Erkennen der indischen Arten in ihren Gattungen stehen zur Verfügung. Nomenklatorische Handlungen ateritarsus Bhattacharyay, Ali & Chaudhuri, 1991 (Cricotopus (Isocladius)), spec. n. lehmanni Bhattacharyay, Ali & Chaudhuri, 1991 (Eukiefferiella), spec. n. saccularis Bhattacharyay, Ali & Chaudhuri, 1991 (Eukiefferiella), spec. n. androgynus Bhattacharyay, Ali & Chaudhuri, 1991 (Orthocladius (Eudactylocladius)), spec. n. deflectus Bhattacharyay, Ali & Chaudhuri, 1991 (Orthocladius (Orthocladius)), spec. n. uniradialis Bhattacharyay, Ali & Chaudhuri, 1991 (Orthocladius (Orthocladius)), spec. n. bicornuatus Bhattacharyay, Ali & Chaudhuri, 1991 (Rheocricotopus (Psilocricotopus)), spec. n. frequens Bhattacharyay, Ali & Chaudhuri, 1991 (Rheocricotopus (Psilocricotopus)), spec. n.